(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Vital to the hypothetical structure is a small scale authentic approach and the juxtaposition of both limited and wide degree, zooming from one singular hero out to his neighborhood environment and networks and farther to Icelandic scribal and scholarly culture all in all. The extent of the proposal can be portrayed as far as four concentric circles the individual, his cozy network, Icelandic culture, and the more extensive European and worldwide setting during the ’post-Gutenberg a period’.